Distance Relay Setting for One Zone of Transmission Line - Kamal Mohammed Mejdhab; Ali N. Hamoodi (NTU Journal of Engineering and Technology)
The objective of this work is to determine the fault location for one zone. Impedance relays constitute a vital component of power systems, specifically within the real value of transmission system, which was accomplished through the utilization of MATLAB/SIMULINK. The sim power system toolbox was employed to enable the intricate modeling of the distance relay, transmission line, and fault simulation. Within the modeling phase, the specific fault type chosen was single line to ground (SLG), Line-to-Line, while the protection scheme was established as the impedance type distance characteristic. This technique represents an interactive simulation environment that facilitates the design and evaluation of relaying algorithms. Moreover, the fundamental principles governing digital distance relays, as well as several pertinent filtering techniques, are meticulously elucidated within the confines of this paper. In order to enhance the user experience and ensure ease of interaction, thereby augmenting the functionality of the developed model. It is important to note that distance or impedance relays constitute a vital component of power systems, specifically within the realm of transmission systems. Finaly, it has been concluded that the fault impedance became less than the set value and a trip signal sent with short time to the circuit breaker.